2014
DOI: 10.1186/1756-0500-7-633
|View full text |Cite
|
Sign up to set email alerts
|

Long-term storage of blood RNA collected in RNA stabilizing Tempus tubes in a large biobank – evaluation of RNA quality and stability

Abstract: BackgroundEstablishing methods for secure long term storage of RNA is critical to realizing the promise of biobanks in biomedical research. Here, we describe the results of yearly analyses of the same set of umbilical cord and adult whole blood RNA collected in Tempus Blood RNA tubes and stored at -80°C, over a period of up to six years. We systematically investigated the effects of long-term storage of samples (75 Tempus tubes form three adult donors and 30 Tempus tubes from three cord blood donors) on the RN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
32
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 41 publications
(39 citation statements)
references
References 23 publications
5
32
0
1
Order By: Relevance
“…Participants were recruited from all over Norway from 1999 to 2008, and the cohort now includes more than 114.500 children, 95.200 mothers, and 75.200 fathers [12]. Biological material in the form of whole blood and plasma has been collected from the mother, the father, and the child (umbilical cord blood) and stored in the biobank, together with extracted DNA, for future use [16,20,21].…”
Section: Study Population and Sample Collectionmentioning
confidence: 99%
See 1 more Smart Citation
“…Participants were recruited from all over Norway from 1999 to 2008, and the cohort now includes more than 114.500 children, 95.200 mothers, and 75.200 fathers [12]. Biological material in the form of whole blood and plasma has been collected from the mother, the father, and the child (umbilical cord blood) and stored in the biobank, together with extracted DNA, for future use [16,20,21].…”
Section: Study Population and Sample Collectionmentioning
confidence: 99%
“…However, reliable quantification of mRNA and miRNA levels requires high-quality RNA, and compromised RNA integrity has been shown to influence such quantification [13][14][15]. Previously, we reported that intact and high-quality RNA suitable for mRNA profiling analyses was obtained from blood samples collected in Tempus tubes and stored at -80˚C over a period of up to six years [16]. Different RNA isolation methods have also been compared for quality and yield when isolating from blood samples collected in Tempus tubes and stored in biobanks [17].…”
mentioning
confidence: 99%
“…The procedures and testing to establish a practical protocol for sampling, handling, transportation and storage of blood RNA is described elsewhere (8). Recently, also the effects of long-term storage of blood RNA collected in RNA stabilizing Tempus tubes was reported (9).…”
Section: Umbilical Cord Samplesmentioning
confidence: 99%
“…It was also demonstrated that the same strategy was applicable for the detection of erythropoietin stimulating agents in micro‐doses . RNA stabilized blood tubes such as Tempus™ blood RNA tubes are mainly used for multi‐site clinical studies in order to facilitate the transport and storage of samples . Indeed, Tempus™ tubes are stable at room temperature for up to five days, unlike EDTA tubes that have to be kept at 4°C and analysed within 48 hours after collection.…”
Section: Introductionmentioning
confidence: 99%
“…[2] RNA stabilized blood tubes such as Tempus ™ blood RNA tubes are mainly used for multi-site clinical studies in order to facilitate the transport and storage of samples. [3,4] Indeed, Tempus ™ tubes are stable at room temperature for up to five days, unlike EDTA tubes that have to be kept at 4°C and analysed within 48 hours after collection. Theoretically, reticulocyte messenger RNA (mRNA) biomarkers could complement the already existing athlete biological passport (ABP) variables and provide additional evidence for blood manipulation.…”
Section: Introductionmentioning
confidence: 99%